Design and construction of telegram bot-based data breach preprocessing application for cyber threat intelligence in institution x - Gandhara, Seto; Satria, Tegar Pandu; Saragih, Hondor (Institute of Computer Science (IOCS), 2025)
Data breaches pose a significant threat in today's digital landscape, especially for organizations handling sensitive information, such as government institutions. These incidents can result in serious consequences, including risks to national security, loss of public trust, and financial harm. Institution X, an Indonesian organization dedicated to cyber threat prevention, faces challenges due to the high volume of unstructured and